1969
DOI: 10.1017/s0022029900012966
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultra-high-temperature (UHT) processing and of subsequent storage on the vitamin content of milk

Abstract: SummaryThe vitamin content of ultra-high-temperature (UHT) processed milk was compared with that of the original raw milk. Three processes were used. In the first, which caused no change in oxygen content, the milk was heated and cooled in a plate-type heat exchanger. In the second, the milk was again heated indirectly and then evaporatively cooled, leaving in the milk about one-third of the initial oxygen content. In the third process the milk was heated by direct steam injection and cooled by evaporation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 11 publications
(9 reference statements)
5
37
0
1
Order By: Relevance
“…The concentration of riboflavin was not influenced by the type of UHT treatment used, which was expected in view of its reported high heat stability (Ga men et al, 1989). The concentrations of thiamine in the UHT milk samples were about half that of the value reported (Fink and Kessler, 1985) for raw milk (35-45 mg/L), concurring with the reported heat sensitivity of this vitamin (Ford et al, 1969;Burton et al, 1970).…”
Section: Compositionsupporting
confidence: 89%
See 1 more Smart Citation
“…The concentration of riboflavin was not influenced by the type of UHT treatment used, which was expected in view of its reported high heat stability (Ga men et al, 1989). The concentrations of thiamine in the UHT milk samples were about half that of the value reported (Fink and Kessler, 1985) for raw milk (35-45 mg/L), concurring with the reported heat sensitivity of this vitamin (Ford et al, 1969;Burton et al, 1970).…”
Section: Compositionsupporting
confidence: 89%
“…Because control and protein-standardized milk products had approximately the same fat content, the concentration of fatsoluble vitamins was expected to be unchanged, as indeed seemed to be the case; variations in vitamin concentration were probably caused by fluctuations in the concentration of fat. The type of UHT heating had no effect on the concentration of retinol or oe-tocopherol in the milk products, indicating the thermal stability of these vitamins, as documented earlier (Ford et al, 1969;Burton et al, 1970;Le Maguer and Jackson, 1983).…”
Section: Compositionsupporting
confidence: 60%
“…Assays for riboflavin, thiamin, vitamin B 12 and folic acid were carried out as described by Ford et al (1969).…”
Section: Methodsmentioning
confidence: 99%
“…Kon & Watson (1936) had previously demonstrated the latter effect. Ford et al (1969) have shown that in ultra-high-temperature (UHT) treated milk processed by direct heating and containing less than 0-1 ppm of O 2 both ascorbic acid and folic acid were retained during storage. High O 2 content resulted in complete destruction of both vitamins within a few days.…”
mentioning
confidence: 99%
“…DONG & OACE [10] , mostraram que leites submetidos a esterilização e subsequente estocagem apresentaram variada taxa de retenção de folatos (0 -80%), dependendo da raça e tipo de alimentação do animal, das condições do processo, da presença de vitamina C e da concentração de oxigênio durante e após o processo. FORD et al [12], FAVIER et al [11] e RENNER [17] ascórbico protetor e o oxigênio um agente que atua na degradação dos folatos.…”
Section: -Introduçãounclassified